Teleoncology Orientation of Low-Income Breast Cancer Patients during the COVID-19 Pandemic: Feasibility and Patient Satisfaction - Roberta Amparado Miziara; Jonathan Yugo Maesaka; Danielle Ramos Martin Matsumoto; Laura Penteado; Ariane Andrade dos Santos Anacleto; Tarso Augusto Duenhas Accorsi; Karine De Amicis Lima; Eduardo Cordioli; Gabriel Salum D´Alessandro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective The present study aims to assess the feasibility and patient satisfaction of teleoncology orientation in a vulnerable population of breast cancer patients assessed in a government health system during the coronavirus pandemic in 2020. Methods Eligible patients received an invitation to receive remote care to minimize exposure to an environment in which the risk of respiratory infection was present. The means of communication was telephone through an application that allows free conversation with no charge. An anonymous-response questionnaire based on a Likert-type scale was sent through a cell phone application or e-mail directly to each patient or close relative of the patient immediately after teleconsultation. Responses to the questions, which addressed utility, facility, interface quality, interaction quality, reliability, satisfaction, and interest in future evaluation, were compiled and analyzed. Results A total of 176 eligible patients scheduled for consultation were evaluated and 98 were included. Seventy (71.4%) successfully undertook the teleorientation. The questionnaire was submitted by 43 (61.4%) patients. The overall teleoncology orientation was classified as very positive by 41 (95.3%) patients. Specifically, regarding the questionnaire items, 43 (100%) patients scored 4 or 5 (agreed that the teleconsultation was beneficial) concerning the facility, followed by 42 (97.2%) for the interface quality, 41 (95.3%) for both utility and interaction quality, 40 (93%) for satisfaction and interest in future evaluation, and, finally, 39 (90.6%) for reliability. Conclusion Teleoncology orientation of low-income breast cancer patients is most feasible and leads to high patient satisfaction.